Pulmonary Deposition of Radionucleotide-Labeled Palivizumab: Proof-of-Concept Study - Rajapaksa, Anushi E.; Do, Lien Anh Ha; Suryawijaya Ong, Darren; Sourial, Magdy; Veysey, Duncan; Beare, Richard; Hughes, William; Yang, William; Bischof, Robert J.; McDonnell, Amarin; Eu, Peter; Yeo, Leslie Y.; et al. (Frontiers in Pharmacology, 2020)
Objective: Current prevention and/or treatment options for respiratory syncytial virus (RSV) infections are limited as no vaccine is available and prophylaxis with palivizumab is very expensive and requires multiple intramuscular injections over the RSV season. Here we present proof-of-concept data using nebulised palivizumab delivery as a promising new approach for the prevention or treatment of severe RSV infections, documenting both aerosol characteristics and pulmonary deposition patterns in the lungs of lambs. Design: Prospective animal study Setting: Biosecurity Control Level 2-designated large animal research facility at Murdoch Children’s Research Institute, Melbourne, Australia Subjects: Four weaned Border-Leicester/Suffolk lambs at five months of age Interventions: Four Lambs were administered aerosolised palivizumab conjugated to Tc-99m, under gaseous anaesthesia, using either the commercially available AeroNeb Go® or the investigational HYDRA device, placed in-line with the inspiratory limb of a breathing circuit. Lambs were scanned in the single-photon emission computed tomography (SPECT/CT) scanner in the supine position during the administration procedure. Measurements and Main Results: Both the HYDRA and AeroNeb Go® produced palivizumab aerosols in the 1-5µm range with similar median aerosol droplet diameters for the HYDRA (1.84μm, range = 0.54–5.41μm) and AeroNeb Go® (mean = 3.07μm, range = 0.86–10μm). Aerosolised palivizumab was delivered to the lungs at 88.79–94.13% of the total aerosolised amount for all lambs, with a small proportion localised to either the trachea or stomach. No difference between devices were found. Pulmonary deposition ranged from 6.57–9.25% of the total dose of palivizumab, mostly in the central right lung. Conclusions: Aerosolised palivizumab deposition patterns were similar in all lambs, suggesting a promising approach in the control of severe RSV lung infections.